Cognitive, behavioral, and neuroanatomical assessment of two unrelated male children expressing FRAXE. - Abrams, M; Doheny, K; Mazzocco, M; Knight, S; Baumgardner, T; Freund, L; Davies, K; Reiss, A (1997)
Standardized cognitive, behavioral, and neuroanatomical data are presented on 2 unrelated boys with the FRAXE (FMR2) GCC expansion mutation. In the context of normal IQ, both boys had a history of developmental delay, including significant problems with communication, attention, and overactivity. Additionally, one child was diagnosed with autistic disorder. Data from these 2 cases are compared to analogous information from previous reports about individuals with the FRAXE or FRAXA (FMR1) mutation. These comparisons support the idea that FRAXE is associated with nonspecific developmental delay and possibly high-functioning autism.